Տեքստի կապակցման միջոցների գործածությունը հուշագրության մեջ - Բարսեղյան, Ա. Գ.
Текст представляет собой связное целое, реализуемое определенными средствами и способами, полностью обусловленное материальной идеей. Исследуя лингвистические особенности строения последнего, мы заметили, что связи предложений, составляющих абзац, ближе, чем связи отдельных абзацев, их связи даже ближе, чем соединения отдельных частей. Это обусловлено большей независимостью предложений. The text is a coherent whole, realized by certain means and methods, conditioned entirely by the material and idea. Introducing, examining the linguistic features of the structure of the latter, we noticed that the connections of the sentences that make up the paragraph are closer than the connections of individual paragraphs, their connections are even closer than the connections of individual parts. It is conditioned by the more independence of the sentences.
Keywords: Լեզվաբանություն